Pacemaker Implant in a Dog with Sick Sinus Syndrome - Aleixo, Amanda Sarita Cruz; Alfonso, Angélica; Kichise, Bárbara Keiko; Neto, Francisco Teixeira; Girotto, Carolina Hagy; Garzesi, André Monti; Garcia, Leonardo Rufino; de Andrade, Rubens Ramos; Lourenço, Maria Lúcia Gomes (Acta Scientiae Veterinariae, 2017)
Background: Sick sinus syndrome is characterized by the presence of arrhythmias, including persistent sinus bradycardia, sinus arrest and paroxysmal atrial tachyarrhythmia. It commonly occurs in elderly dogs, especially miniature schnauzers; however, it is also detected in dachshunds and pugs. Reports of clinical signs by animal owners are not always clear and precise, which may result in erroneous interpretations by veterinarians; consequently, the use of inappropriate therapies. The present work aims to describe clinical aspects and findings from tests related to sick sinus syndrome (SSS) and presents the case of a female schnauzer with SSS. Case: A 10-year-old female dog (schnauzer, 8.6 kg) attended the Veterinary Hospital of the FMVZ-UNESP - Botucatu. The owner mentioned convulsive episodes, but a thorough medical history and patient assessment revealed that the dog exhibited episodes of syncope. During the physical examination, cardiac auscultation revealed the heart rate to be 56 beats per minute (bpm), and there was a presence of pauses. Also during cardiac auscultation, a holosystolic heart murmur was verified, with a focus on the mitral and tricuspid valves. The electrocardiogram showed the presence of sinus arrest with escape rhythms, pauses of 10 s and the presence of bradycardia-tachycardia syndrome. A Holter monitor was used to establish the diagnosis of SSS. The patient presented with significant episodes of syncope during outpatient care, and based on the clinical manifestation, drug therapy was initiated. The prescribed medications were aminophylline 20 mg/ kg TID, enalapril maleate 0.5 mg/kg BID, spironolactone 1 mg/kg SID and furosemide 2 mg/kg BID. After the start of treatment, there was a reduction in the frequency of episodes of syncope. Three weeks after diagnosis, a pacemaker device was implanted. Currently, clinical signs are absent. Discussion: Sinus node dysfunction is one of the main reasons for pacemaker implantation. It is usually diagnosed based on clinical signs and the presence of sinus bradycardia and sinus pauses in electrocardiograms or Holter monitoring. The diagnosis of SSS is limited to cases in which the patient does not present with abnormalities in an electrocardiogram. Syncope is a clinical sign commonly present in patients with dysfunction of the sinus node, and episodes of syncope were reported by the owner of the dog referred to in the present report. A thorough medical history and physical examination must be performed to diagnose SSS because erroneous diagnosis and incorrect interpretations of clinical signs can lead to the misuse of medications. The treatment of choice for SSS is an implantable pacemaker device; however, because the method is not widely used in Brazil, a second option is drug treatment. In the present report, after implantation of a pacemaker, clinical signs ceased, and the patient was in good general health and could return to her normal activities. Sick sinus syndrome is a disease commonly found in schnauzers. There is a need for detailed histories and complementary exams because the clinical signs do not always correlate with electrocardiographic findings. The implantation of a pacemaker is the treatment of choice and is effective for the condition, but its use is not uniformly accessible throughout the country.